State Hegemony in the Campaign of Religious Moderation in Higher Education (a Study at UIN Walisongo Semarang and UIN Raden Mas Said Surakarta) - Muhammad, Hasyim; Naili Ni'matul Illiyyun (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2023)
Religious radicalism in the university has recently reached a serious level. Not a few academics are involved in this understanding and show extreme attitudes both at the level of action and narrative. Since 2019, the Ministry of Religious Affairs has been committed to strengthening religious moderation. These efforts can be seen concretely in the preparation of Religious Moderation books, counseling activities, the formation of educational curriculum, and the establishment of the House of Religious Moderation in universities. PTKIN as the long arm of the Ministry of Religious Affairs has a strategic role in mainstreaming religious moderation in Indonesia. This qualitative study took two PTKIN in Central Java, UIN Walisongo Semarang and UIN Raden Mas Said Surakarta. Using a descriptive narrative approach, this study aims to determine the basis of the argumentation for mainstreaming religious moderation, identify activities initiated by PTKIN, and the practice of state hegemony through the Ministry of Religious Affairs in this effort. The results of this study indicate that UIN Walisongo Semarang and UIN Raden Mas Said Surakarta have theological and cultural argumentation bases in mainstreaming religious moderation. Both campuses have initiated activities both academic and non-academic in the implementation of religious moderation. In addition, the state through the Ministry of Religious Affairs seems to be aggressive in preventing radicalism and extremism by giving a mandate to PTKIN in mainstreaming religious moderation which seems to indicate that Islam is separate from the value of moderation.